2022
DOI: 10.1021/acsapm.1c01606
|View full text |Cite
|
Sign up to set email alerts
|

All-Organic Electroactive Shape-Changing Knitted Textiles Using Thermoprogrammed Shape-Memory Fibers Spun by 3D Printing

Abstract: Here, we present knittable shape-memory polymeric fibers extruded using a 3D-printer nozzle-based melt-spinning method for high throughput of composition and condition testing. These structures are used as the basis for electroactive shape-changing knitted textiles combining several types of fibers, including organic fibrous heaters. These structures represent a different approach to “on-demand” shape-memory fibers and can be incorporated into a variety of textile architectures, including inlaid knitting, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As key components, textile-based actuators have been used in many wearable devices, such as devices to assist human movement, and smart clothing for regulating human comfort. Textile actuator implementation typically occurs in two ways: one is sewing stimulus-responsive fibers into everyday textiles, , and the other is weaving or knitting fiber actuators directly into fabrics . As examples, Figure a demonstrates how active liquid crystal elastomer (LCE) yarns, combined with conventional textile yarns, produce textiles capable of contract/relax and 3D deformations …”
Section: Structures Of Fiber/textile Actuatorsmentioning
confidence: 99%
“…As key components, textile-based actuators have been used in many wearable devices, such as devices to assist human movement, and smart clothing for regulating human comfort. Textile actuator implementation typically occurs in two ways: one is sewing stimulus-responsive fibers into everyday textiles, , and the other is weaving or knitting fiber actuators directly into fabrics . As examples, Figure a demonstrates how active liquid crystal elastomer (LCE) yarns, combined with conventional textile yarns, produce textiles capable of contract/relax and 3D deformations …”
Section: Structures Of Fiber/textile Actuatorsmentioning
confidence: 99%
“…Printing on textile fabric is strongly related with parameters of 3D printer and textile used as base substrate [19,20]. Despite created for aesthetic [21] or functional purpose [22,23], one of the main problems encountered with the composite structure is adhesion between textile fabric and 3D printed material [24,25]. From the literature surveyed there is a high number of papers published dealing with test of adhesion of printed material on textile fabrics [26].…”
Section: Introductionmentioning
confidence: 99%
“…The temporary shape can be maintained for a long time by cooling down below T trans and then the permanent shape can be automatically recovered upon reheating above T trans . Recently, SMPs and their composites have been applied in many fields including aerospace, biomedicine, textiles, and electron devices. So far, SMPs including polyurethane (PU), cyanate, , epoxy, polylactic acid, polyimide, , polyaryletherketone, and rubber , have been reported. However, the study of shape memory phenol-formaldehyde (SMPF) resin is rarely reported. , …”
Section: Introductionmentioning
confidence: 99%